2020
DOI: 10.14202/vetworld.2020.2294-2300
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the hematological and clinical biochemical markers of stress in broiler chickens

Abstract: Background and Aim: Stress significantly affects health and productivity of animals. There is need for affordable and easy-to-assay markers of physiological stress in broilers. This study evaluated hematological and serum biochemical markers of physiologic stress in broiler chickens. Materials and Methods: Thirty day-old broiler chickens were assigned to three groups of ten broilers each during the 56-day study. Group 1 broilers served as the control and were not exposed to any stressors; Group 2 broilers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
19
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 43 publications
6
19
0
6
Order By: Relevance
“…By contrast, our present findings showed that a high stocking density could be associated with increased levels of leukocytes and lymphocytes in broilers. Similar to our results, Nwaigwe et al (2020) showed an increase in leukocytes and lymphocytes with increasing stocking density stress. The researchers thus suggested that stress due to a high stocking density may increase the activity of noradrenaline, which can activate the generation of hematopoietic stem cells, especially leukocytes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…By contrast, our present findings showed that a high stocking density could be associated with increased levels of leukocytes and lymphocytes in broilers. Similar to our results, Nwaigwe et al (2020) showed an increase in leukocytes and lymphocytes with increasing stocking density stress. The researchers thus suggested that stress due to a high stocking density may increase the activity of noradrenaline, which can activate the generation of hematopoietic stem cells, especially leukocytes.…”
Section: Discussionsupporting
confidence: 92%
“…The present study clearly showed that the serum concentration of albumin is higher in chicks raised at a high stocking density than in those reared at a low stocking density. Similar to our findings, Nwaigwe et al (2020) and Jeong et al (2020) revealed that serum albumin concentrations increase in broilers reared at a high stocking density. Indeed, an increase in serum albumin level is a good indicator of physiological stress in broiler chickens (Nwaigwe et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Leukocyte formula (El-Lethey et al, 2000;Jiang et al, 2017;Liew & Kubes, 2019) and the concentration of hormones in the blood (Scanes, 2016;Weimer et al, 2018) are usually used to diagnose stress, as well as the characteristics of hens' adaptation processes. Recently, some biochemical markers of blood serum have been actively used in poultry (Nwaigwe et al, 2020;Ruiz-Jimenez et al, 2021), which, in contrast to the leukocyte formula and hormonal status, allow us to describe the general physiological state of the body, adaptation processes (Kraus et al, 2021) and diagnose metabolic disorders of organs and tissues (Kudair & Al-hussary, 2010;Koronowicz et al, 2016). In general, serum biochemical markers are indicators of hens' health and reflect any physiological or even pathological changes occurring in their body (Koronowicz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Відомо, що під час стресу у курей напружується діяльність усіх систем організму, яка спрямовується на самозахист і пристосування до нових умов існування (Olubodun et al, 2015;Infante et al, 2017;Shevchuk et al, 2018). Останнім часом для діагностики стресових станів у птиці почали активно використовувати деякі біохімічні параметри сироватки крові (Nwaigwe et al, 2020;Ruiz-Jimenez et al,2021), які, на відміну від лейкоцитарної формули та гормонального статусу, дозволяють описати загальний фізіологічний стан організму, процеси адаптації (Kraus et al, 2021) та діагностувати метаболічні порушення органів і тканин (Al-Hussary & Kudair, 2010;Koronowicz et al, 2016). Загалом, біохімічні параметри сироватки крові є надійними показниками стану здоров'я курей і відображають будь-які фізіологічні чи навіть патологічні зміни, що відбуваються в їх організмі (Koronowicz et al, 2016).…”
unclassified